Virus‐neutralising antibody responses in horses following vaccination with Equivac® HeV: a field study. Issue 5 (24th April 2018) - Tan, RHH; Hodge, A; Klein, R; Edwards, N; Huang, JA; Middleton, D; Watts, SP
Abstract : Objective: To determine the antibody responses to a commercial Hendra virus vaccine (Equivac® HeV) in a field environment. Methods: A group of 61 horses received a primary vaccination course comprising two doses administered 3–6 weeks apart (V1, V2) and a 3rd dose (V3) given 6 months after the second. This was followed by booster vaccinations at 12 monthly intervals (V4, V5). Antibody titres were assessed using a virus‐neutralisation test. Results: Neutralising antibodies against HeV were not detected prior to vaccination. Antibodies were detected in 54/57 horses at 3 weeks after V1 and 51/51 had titres ≥ 32 at 8 weeks after V2. At 6 months after V2, antibody titres decreased in most (31/34) horses and were not detected in three horses. A rapid increase in antibody titres was recorded in 35/36 horses at 1 week following V3. By the first annual booster vaccination (V4), antibodies were still detectable in 29/29 horses, although titres had decreased; in 26/29 horses, titres remained ≥ 32. All horses showed an increase in antibody titres after V4. There was no statistically significant increase in mean antibody titre after V5, compared with after V4. Conclusion: Horses administered Equivac® HeV, using a primary vaccination course followed by annual booster vaccinations, mounted an effective secondary immune response and acquired antibody responses that were consistent with protective immunity against HeV in the form of virus‐neutralising antibodies. No adverse events were observed after vaccine administration.